Sectarianism in the Scottish Labour Market; what the 2011 Census Shows. Issue 2 (May 2017) - Bruce, Steve; Glendinning, Tony
Abstract : As disadvantage can have causes other than discrimination, its presence cannot prove discrimination. However, the absence of patterns of disadvantage in large data sets would be very strong evidence against the presence of sectarian discrimination. In this paper we analyse data on religion, social class, education, gender and region from the 2011 Scottish census. Against those who argue that sectarianism is endemic in the west of Scotland, we find no sectarian association between religion and social class among people at the peak age of their labour market involvement. The class profiles of people in the Other Religion categories are unusual but the profile for Catholics is pretty much the same as for Other Christians. That this analysis involves 487, 694 people gives us confidence that the results are robust. Hence we conclude there is no evidence that the Scottish labour market is characterised by sectarian discrimination. We would like to acknowledge the assistance of the staff of the office of the Registrar General for Scotland who kindly provided us with the census data.